Loose Leaf for Talaro's Foundations in Microbiology: : Basic Principles - Chess, Barry (New York, NY : McGraw Hill LLC, 2024)
"Barry Chess has taught microbiology at Pasadena City College for more than 20 years. Prior to that, while studying at the California State University and the University of California, he conducted research into the expression of genes involved in the development of muscle and bone. At PCC, beyond his usual presence in the microbiology laboratory and lecture hall, Barry has taught majors and non-majors biology, developed a course in human genetics, helped to found a biotechnology program on campus, and regularly supervises students completing independent research projects in the life sciences. Of late, his interests focus on innovative methods of teaching that lead to greater student success. He has written and reviewed cases for the National Center for Case Study Teaching in Science and contributed to the book Science Stories You Can Count On: 51 Case Studies with Quantitative Reasoning in Biology. Barry has presented papers and talks on the effective use of case studies in the classroom, the use of digital tools to enhance learning, and for several years served as a scientific advisor for the American Film Institute. In addition to Foundations in Microbiology, Barry is the author of Laboratory Applications in Microbiology, A Case Study Approach, now in its fourth edition. He is a member of the American Association for the Advancement of Science, the American Society for Microbiology, and the Skeptics Society. When not teaching or writing, he spends as much time as possible skiing, diving, or hiking with Toby, his 110-pound pandemic puppy. Barry was profiled in the book What Scientists Actually Do, where he was illustrated as a young girl with pigtails, about to stick a fork into an electrical outlet"--
Includes index.
Keywords: Microbiology; Medical microbiology